2009
DOI: 10.1158/1078-0432.ccr-09-1024
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study Comparing the Tolerability and Efficacy of Ipilimumab Administered with or without Prophylactic Budesonide in Patients with Unresectable Stage III or IV Melanoma

Abstract: Purpose: Diarrhea (with or without colitis) is an immune-related adverse event (irAE) associated with ipilimumab. A randomized, double-blind, placebo-controlled, multicenter, multinational phase II trial was conducted to determine whether prophylactic budesonide (Entocort EC), a nonabsorbed oral steroid, reduced the rate of grade ≥2 diarrhea in ipilimumab-treated patients with advanced melanoma. Experimental Design: Previously treated and treatment-naïve patients (N = 115) with unresectable stage III or IV mel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
345
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(368 citation statements)
references
References 40 publications
15
345
0
8
Order By: Relevance
“…However, these modalities are still largely suboptimal and carry substantial immune toxic effects in the skin, gastrointestinal tract, and other syndromes such as uveitis or hypophysitis (31)(32)(33). This occurs because anti-CTLA4 and anti-PD1 target general immune checkpoints, which are not tumor-specific, although those caused by anti-PD1 seem to be milder (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, these modalities are still largely suboptimal and carry substantial immune toxic effects in the skin, gastrointestinal tract, and other syndromes such as uveitis or hypophysitis (31)(32)(33). This occurs because anti-CTLA4 and anti-PD1 target general immune checkpoints, which are not tumor-specific, although those caused by anti-PD1 seem to be milder (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…CLTA4 (cytotoxic T-lymphocyte antigen 4) is a ligand receptor associated with B7.2, and functions as a negative regulator of T-cell activation. Two anti-CTLA4 monoclonal antibodies, tremelimumab and ipilimumab, have shown promise in initial clinical trials, [154][155][156][157] and a randomized phase III trial recently demonstrated a 3.7-month survival benefit in patients with metastatic melanoma who received ipilimumab versus glycoprotein 100 peptide vaccine. 158 As more is learned about the anticancer immune response and the mechanisms of immune evasion and modulation utilized by primitive melanoma cells, further immunotherapeutic targets will be identified.…”
Section: Translational Relevance Of Melanoma Stem Cellsmentioning
confidence: 99%
“…Immunotherapy most frequently results in GI and skin irAEs because these are the sites that are exposed to the commensal flora [57]. Blockade of CTLA-4 will result in dysregulation of GI mucosal immunity as evidenced by fluctuating antibody titers to enteric flora, increased levels of neutrophil-derived fecal calprotectin, and inflammatory infiltration into the mucosa.…”
Section: Discussionmentioning
confidence: 99%